Addressing climate risks mainstreaming climate change in development project planning and budgeting in Bangladesh - Perveen, MST Farida; Nahar, Nurun; Chowdhury, Farhat Jahan; Osti, Rabindra (ADB Briefs)
This brief shows how Bangladesh can improve development planning and boost resilience by comprehensively analyzing climate and disaster risk to better calculate possible economic losses and implement effective adaptation measures.